1990
DOI: 10.1038/jcbfm.1990.18
|View full text |Cite
|
Sign up to set email alerts
|

Influence of MK-801 on Brain Extracellular Calcium and Potassium Activities in Severe Hypoglycemia

Abstract: Summary:The purpose of the present study was to ex amine the effect of blockade of N-methyl-o-aspartate (NMDA) receptors on the depolarization associated with severe hypoglycemia, which is commonly preceded by one or a few transient depolarizations reminiscent of cor tical spreading depression (CSD). In the cerebral cortices of rats [K + le and [Ca2 + le were measured with ion selective microelectrodes. NMDA blockade was achieved by injection of MKSOI in doses that block CSD. In control rats, the latency from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 17 publications
1
28
0
Order By: Relevance
“…Conversely, changes in extracellular divalent cations may have dramatic effects on physiological neuronal function (Kuwana et al, 1998;Hsu et al, 2000). The concentrations of extracellular divalent cations have also been shown to undergo large changes in association with pathological states such as ischemia, hypoglycemia, or seizures (Harris and Symon, 1984;Somjen and Giacchino, 1985;Silver and Erecinska, 1990;Zhang et al, 1990;Kristian et al, 1993;Altura et al, 1997;Szilagyi et al, 2000). Both low Ca 2ϩ and low Mg 2ϩ can evoke seizure activity (Leschinger et al, 1993;Bikson et al, 1999;Buchheim et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, changes in extracellular divalent cations may have dramatic effects on physiological neuronal function (Kuwana et al, 1998;Hsu et al, 2000). The concentrations of extracellular divalent cations have also been shown to undergo large changes in association with pathological states such as ischemia, hypoglycemia, or seizures (Harris and Symon, 1984;Somjen and Giacchino, 1985;Silver and Erecinska, 1990;Zhang et al, 1990;Kristian et al, 1993;Altura et al, 1997;Szilagyi et al, 2000). Both low Ca 2ϩ and low Mg 2ϩ can evoke seizure activity (Leschinger et al, 1993;Bikson et al, 1999;Buchheim et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The complexity of CSDs is further exempli fied by the fact that these CSDs that are evoked in the cortex by bipolar stimulation are completely blocked by MK-801 whereas only a partial effect was seen in the ischaemic penumbra in the present study. Also, under conditions of severe hypogly caemia, MK-801 was unable to block the CSDs (Zhang et al, 1990) in spite of its ability to amelio rate the hypoglycaemia-induced neuronal degener ation (Westerberg et aI., 1988). In a hypoxic hip pocampal slice preparation, Radar and Lanthorn (1989) demonstrated that persistent depolarisation could be blocked by MK-801 but not the initial de polarisation.…”
Section: Discussionmentioning
confidence: 99%
“…The changes in ACSF ionic composition may enhance NMDAreceptor-dependent synaptic transmission, reduce calciumdependent potassium currents, and reduce short-term synaptic depression, relative to that observed with standard ACSF. The modified ACSF is, in some respects, more similar to in vivo rodent CSF than to standard ACSF (16,17). We have shown previously that experience-dependent changes in circuit excitability can be readily revealed under these ''active-slice'' conditions (10).…”
Section: Reduced Circuit Activity In L5 Pyramidal Neurons Of Mecp2-numentioning
confidence: 99%